Demographic, risk factors, and management practices of patients with acute coronary syndrome: an observational study in a tertiary care hospital in Central India - Chinmay Guralwar; Harshwardhan Khandait; Prabhav Tekam; Antara Agrawal; Rashi Mahajan; Nandita Gawande; Vinod Khandait (MGM Journal of Medical Sciences)
Background: Acute coronary syndrome (ACS) remains a major cause of mortality worldwide, with India reporting approximately three million cases annually. This study aims to assess the demographics, risk factors, and treatment patterns of ACS patients in Central India while exploring challenges related to pre-hospital delays and financial constraints. Materials and Methods: A cross-sectional, questionnaire-based study was conducted at a tertiary care hospital. Data from patients with ACS were collected through face-to-face interviews using a self-designed, semi-structured, open-ended questionnaire. Results: Among the 90 participants, 86.6% were diagnosed with an acute ST-segment elevation myocardial infarction (STEMI), with a male predominance (81.1%). Common risk factors included smoking, diabetes, hypertension, and a history of cardiovascular events. The primary reasons for delays in seeking medical care were a lack of recognition of symptom severity (37%), prolonged travel times (21%), and unavailability of suitable transportation (21%). Chest pain was the most frequently reported initial symptom (73.3%), with symptom onset occurring most often in the morning (43.3%). Males were more likely to experience anterior wall MI, while females predominantly presented with inferior or posterior wall MI. Emergency medical service (EMS) utilization was low, with most patients relying on personal vehicles for transportation. Additionally, rural patients required at least one additional hospital visit before reaching the tertiary care center compared to their urban counterparts. Thrombolysis was the primary treatment modality, administered to 76.67% of participants, with an average door-to-needle time of 78 ± 63 min. Conclusion: Multiple hospital referrals and inadequate EMS utilization hinder optimal ACS management. This study underscores the need for a streamlined referral process, enhanced EMS infrastructure, reduced door-to-needle time, and targeted interventions to mitigate financial barriers to ACS care in India.